2004
DOI: 10.1007/s10114-003-0307-x
|View full text |Cite
|
Sign up to set email alerts
|

Non-Zero Degree Maps Between 2n-Manifolds

Abstract: Abstract. Thom-Pontrjagin constructions are used to give a computable necessary and sufficient condition when a homomorphism φ :and L, n > 1. A corollary is that each (n − 1)-connected 2n-manifold admits selfmaps of degree larger than 1, n > 1.In the most interesting case of dimension 4, with the additional surgery arguments we give a necessary and sufficient condition for the existence of a degree k map from a closed orientable 4-manifold M to a closed simply connected 4-manifold L in terms of their intersect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 6 publications
1
41
0
Order By: Relevance
“…This result fails in dimension four, by a recent work of Pankka and Souto [19], where it is shown that T 4 is not a branched covering of # 3 (S 2 × S 2 ), while every integer can be realized as the degree for a map from T 4 to # 3 (S 2 × S 2 ) (by a criterion of Duan and Wang [8]; see Section 5.2).…”
Section: Theorem 4 Every Simply Connected Closed Four-manifold M Admentioning
confidence: 86%
See 2 more Smart Citations
“…This result fails in dimension four, by a recent work of Pankka and Souto [19], where it is shown that T 4 is not a branched covering of # 3 (S 2 × S 2 ), while every integer can be realized as the degree for a map from T 4 to # 3 (S 2 × S 2 ) (by a criterion of Duan and Wang [8]; see Section 5.2).…”
Section: Theorem 4 Every Simply Connected Closed Four-manifold M Admentioning
confidence: 86%
“…Nevertheless, we note that T 2 × Σ k is a branched four-fold cover of # k (S 2 × S 2 ), by Remark 2. The existence of dominant maps from products T 2 × Σ k to every simply connected four-manifold has also been shown by Kotschick and Löh [15], using a result of Duan and Wang [8]. That result states that if X and Y are oriented, closed four-manifolds and Y is simply connected, then a degree d = 0 map f : X −→ Y exists if and only if the intersection form of Y , multiplied by d, is embedded into the intersection form of X, where the embedding is given by H * (f ) (the "only if" part is obvious).…”
Section: Branched Coverings In Dimension Fourmentioning
confidence: 91%
See 1 more Smart Citation
“…This is not a problem when the dimension is three. In dimension four, Duan and Wang [12] show that, when we are working on continuous maps and topological manifolds, the simply connected 4-manifolds are ordered by their intersection forms. There are topological 4-manifolds not admitting smooth structures.…”
Section: Geometric Structures Gromov Norm and Kodaira Dimensions 21mentioning
confidence: 99%
“…However, we have f : M 1 #kCP 2 → CP 2 #5CP 2 with k ≥ 5. There is no such map for k < 5 since they are simply connected which is ordered by their intersection forms by [12].Notice that Theorem 5.1 is related to (and could be viewed as 0-dimensional generalization of) the Iitaka conjecture, which states that a fiber space f : X → Z satisfies κ h (X) ≥ κ h (Z) + κ h (F ) where F is a general fiber of f . Here, an (analytic) fiber space is a proper surjective morphism with connected fibres.…”
mentioning
confidence: 99%